Progression of Blood Pressure and Cardiovascular Outcomes in Hypertensive Patients in a Reference Center - Guimarães Filho,Gilberto Campos (2015)
Background: Hypertension is a public health problem, considering its high prevalence, low control rate and cardiovascular complications. Objective: Evaluate the control of blood pressure (BP) and cardiovascular outcomes in patients enrolled at the Reference Center for Hypertension and Diabetes, located in a medium-sized city in the Midwest Region of Brazil. Methods: Population-based study comparing patients enrolled in the service at the time of their admission and after an average follow-up of five years. Participants were aged ≥18 years and were regularly monitored at the Center up to 6 months before data collection. We assessed demographic variables, BP, body mass index, risk factors, and cardiovascular outcomes. Results: We studied 1,298 individuals, predominantly women (60.9%), and with mean age of 56.7±13.1 years. Over time, there was a significant increase in physical inactivity, alcohol consumption, diabetes, dyslipidemia, and excessive weight. As for cardiovascular outcomes, we observed an increase in stroke and myocardial revascularization, and a lower frequency of chronic renal failure. During follow-up, there was significant improvement in the rate of BP control (from 29.6% to 39.6%; p = 0.001) and 72 deaths, 91.7% of which were due to cardiovascular diseases. Conclusion: Despite considerable improvements in the rate of BP control during follow-up, risk factors worsened and cardiovascular outcomes increased.